Going beyond the potential equifinality problems: A response to Saladié and Rodríguez-Hidalgo (2019) - Rosell, Jordi; Blasco, Ruth; Arilla, Maite; Fernández-Jalvo, Yolanda (Quaternary International, 2019)
Actualistic studies have been commonly used as valid analogies in taphonomic research and, as the growing body of data demonstrate, have proved to be highly informative to explain the formation of terrestrial vertebrate fossil faunas. In Rosell et al. (2019), we conducted an experimental study with free-ranging brown bears (Ursus arctos arctos) with the aim of modeling their behavior and characterizing the bone damage caused on large, medium and small-sized ungulate carcasses. The purpose of the study was to highlight the equifinality processes observed experimentally based on the assumption that “some carnivores show physical and dental characteristics that could lead to bone modifications potentially like those generated by humans” (Rosell et al., 2019, p.67). In the case of bears, their “bunodont dentition and plantigrade locomotion –the latter allows them to frequently release and use their claws as ‘hands’”– have led to the production of peeling and tooth marks that show important similarities with those generated during the feeding activities of humans and chimpanzees (Pan troglodytes), although anecdotally also made by other taphonomic agents. Saladié and Rodríguez-Hidalgo (2019) interpret our study as an attempt to invalidate their inferences about human tooth marks from the TD6.2 level of Gran Dolina (Sierra de Atapuerca, Burgos, Spain), even though we do not make any archaeological application. We also clearly maintain that ours is an initial and merely descriptive study that aims to raise awareness of the existence of taphonomic equifinality phenomena between bears and humans. The present work intends, therefore, to respond to their criticisms about the contexts in which humans and bears produce peeling as well as about the methodology used for assessing the tooth mark measurements. We have tried to read positively the Saladié and Rodríguez-Hidalgo's (2019) paper in order to make progress in the main challenge of finding elements and features that allow us to discriminate bone alterations potentially ...